2020
DOI: 10.1039/d0nj02125c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and anti-inflammatory activity evaluation of novel chroman derivatives

Abstract: In an effort to develop potent anti-inflammatory agents, a series of novel chroman derivatives including acyclic amidochromans, chromanyl esters and chromanyl acrylates have been designed, synthesized and fully characterized. These...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…On the other hand, chromone derivatives possess many different biological activities such as anticancer [ 31 , 32 , 33 ], antimicrobial [ 34 ], anti-inflammatory [ 35 , 36 ], antitubercular [ 37 , 38 ] and others activities [ 39 , 40 , 41 ], which have generated an interest in developing further this scaffold. The chromone scaffold is also present in some approved drugs such as flavoxate ( Figure 2 ), a muscarinic antagonist and spasmolytic.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, chromone derivatives possess many different biological activities such as anticancer [ 31 , 32 , 33 ], antimicrobial [ 34 ], anti-inflammatory [ 35 , 36 ], antitubercular [ 37 , 38 ] and others activities [ 39 , 40 , 41 ], which have generated an interest in developing further this scaffold. The chromone scaffold is also present in some approved drugs such as flavoxate ( Figure 2 ), a muscarinic antagonist and spasmolytic.…”
Section: Introductionmentioning
confidence: 99%
“…. The above data suggested that 1 would be a chroman derivative, which was similar to N-butyl-2,2-dimethylchroman-6-carboxamide, [20] except for the presence of a Δ 3,4 double bond and the replacement of the ethyl group at C-16 in N-butyl-2,2-dimethylchroman-6-carboxamide by a carboxylic group in 2. 1 2).…”
Section: Introductionmentioning
confidence: 76%
“…The 1 H NMR and 13 C NMR spectroscopic data (Table 2) revealed the presence of two methyls [δ H 1.41 (s, H 3 -11 and H 3 -12); δ C 28.3 (C-11 and C-12)], two methenes [δ H 3.59~3.64 (m, H 2 -15), 2.64 (t, J=6.8 Hz, H 2 -16); δ C 36.5 (C-15, 34.5, C-16)], two olefinic methines [δ H 5.78 (d, J=9.6 Hz, H-3), 6.42 (d, J=9.6 Hz, H-4); δ C 132.2 (C-3, 122.5, C-4)], one oxygenated quaternary carbon [δ C 77.7 (C-2)], two carbonyls [δ C 167.2 (C-13), 173.6, (C-17)], an amino group [δ H 7.72 (br s, 14-NH)], and a trisubtituted benzene ring [δ H 7.59 (br s, H-5), 7.67 (br d, J=8.4 Hz, H-7), 6.75 (d, J=8.4 Hz, H-8); δ C 126.5 (C-5), 128.1 (C-6), 129.2 (C-7), 116.6 (C-8), 156.4 (C-9), 121.6 (C-10)]. The above data suggested that 1 would be a chroman derivative, which was similar to N-butyl-2,2-dimethylchroman-6-carboxamide,[20] except for the presence of a Δ 3,4 double bond and the replacement of the ethyl group at C-16 in N-butyl-2,2-dimethylchroman-6-carboxamide by a carboxylic group in 2 1. H-1 H COSY correlation between H-3 and H-4, and HMBC correlations between H-4/ C-2, H-4/C-5, H-4/C-9, H-4/C-10, H-3/C-10, H 3 -12/C-2, and H 3 -12/C-3 demonstrated the existence of a Δ 3,4 double bond (Figure 2).…”
mentioning
confidence: 78%
“…[16] On the other hand, amides are nitrogen-containing derivatives of carboxylic acids. Amide derivatives play a significant role in pesticide and pharmaceutical industries because of their rich biological activities, including anti-inflammatory, [17] insecticidal, [18,19] herbicidal, [20] antifungal, [21,22] and anticancer activities. [23] Also, thiourea derivatives are widely applied in medicine and agriculture because they hold various biological activities, [24] like antifungal, [25 -27] herbicidal, [28] anti-inflammatory, [29,30] antibacterial, [31] antiviral, [32] and plant growth regulation [33,34] activities.…”
Section: Introductionmentioning
confidence: 99%